Canine Mixed Mammary Tumour as a Model for Human Breast Cancer with Osseous Metaplasia. Issue 4 (May 2017) - Saad, E.S.; Milley, K.M.; Al-Khan, A.A.; Nimmo, J.S.; Bacci, B.; Tayebi, M.; Day, M.J.; Richardson, S.J.; Danks, J.A.
Summary: Canine mixed mammary tumours (CMMTs) and human metaplastic breast carcinomas (HMBCs) share several histopathological features and risk factors. In both species, these tumours display epithelial and stromal components. HMBCs are rare malignant tumours, but CMMTs are one of the most common mammary tumours in dogs and are more often benign than malignant. In this study, benign ( n  = 88) and malignant ( n  = 13) CMMTs were characterized using specific antibodies against oestrogen receptor, progesterone receptor, human epidermal growth factor receptor 2, cytokeratin 5/6, cytokeratin AE1/AE3, vimentin, Ki67, E-cadherin and p63. Cartilage and bone matrices associated with benign and malignant CMMTs were characterized using specific antibodies against BMP4, Runx2, Sox9 and osteopontin. The current study suggested that CMMTs are of epithelial origin, but display a myoepithelial-like differentiation. The findings suggest key roles for Sox9, Runx2 and BMP4 in chondrogenesis and bone formation in CMMTs. The high expression of osteopontin in CMMTs appears to be unrelated to tumour malignancy.